Air pollution tolerance index of plants around brick kilns in Rawalpindi, Pakistan. (1st April 2017) - Achakzai, Khanoranga; Khalid, Sofia; Adrees, Muhammad; Bibi, Aasma; Ali, Shafaqat; Nawaz, Rab; Rizwan, Muhammad
Abstract: In any contaminated environment, the sensitive plant species can serve as bio-indicator of air pollution while tolerant plant species can act as a sink for air pollutants. Air pollution tolerance index (APTI) is an important tool to screen out plants based on their tolerance or sensitivity level to different air pollutants. The present study was aimed to identify the sensitive and tolerant plant species in the vicinity of brick kilns in the Rawalpindi city. To determine the susceptibility level of the selected plant species, four biochemical parameters, ascorbic acid, total chlorophyll content, relative water content and pH of leaf extract, were assessed and APTI was calculated. Plant sampling was carried out with increasing distance of 100, 300 and 500 m around three brick kiln sites and APTI values were calculated by following the standard methods. The results of the study revealed that among nine studied plant species, Calotropis procera (APTI = 20.05) and Althernanthera pungens (APTI = 17.13) were found to be the most tolerant species, whereas Malva neglecta (APTI = 8.83) was found to be the most sensitive species. Inconsistent trend of variations was seen in the APTI values at each site. The present study suggested that the most tolerant species, C. procera and A. pungens, could be grown in the vicinity of such pollution sources as a remedial measure of brick kiln pollution. Highlights: Brick kiln industry has resulted an increase in gaseous pollutants in the atmosphere. APTI could be used to evaluate plant tolerance or sensitivity level. Plant response to air pollution varied with plant species. Plant tolerant species could be grown in the vicinity of brick kilns.